A re-evaluation of the 2010 quantitative understanding of the effects volcanic ash has on gas turbine engines. (October 2016) - Clarkson, Rory J; Majewicz, Elizabeth JE; Mack, Peter
As part of the cross industry efforts to get aircraft flying again during the April/May 2010 eruption of Eyjafjallajokull Rolls-Royce produced a chart that plotted examples of aircraft engine exposure to volcanic ash against the ash concentration the engines had been exposed to. This chart became known as the Rolls-Royce 'Safe-to-Fly' chart, and it was used to guide decisions on how the UK Met Office ash concentration charts for the Eyjafjallajokull eruption could be utilised to help aviators plan their flight paths. Over the period 2011–2013, this paper's authors reassessed the engine data that made up the 'Safe-to-Fly' chart, and in particular the data relating to two key exposure events at high ash concentrations, flight BA009 on 24 June 1982 and flight KLM867 on 15 December 1989. Through a combination of reassessment of the original engineering calculations carried out for these events (i.e. calculations based on evidence from engine hardware) and assessments of relevant volcanological and ash cloud visibility data, it has been concluded that these events are unlikely to have occurred at or near the 2000 mg/m 3 ash concentration arrived at in 2010; based on current evidence, it is more plausible that these events occurred in ash concentrations of around 200 mg/m 3 . As a consequence, a revision to the 'Safe-to-Fly' chart is recommended. In addition, to more easily present the main considerations associated with flight within ash concentrations where the ash would start to become visible, a new chart is proposed that plots duration of exposure against ash concentration. The points plotted on this chart are the revised understanding of the BA009 and KLM867 events, other relevant engine exposure events and speculative regions where flight would be unsafe and where flight would be safe, but engines would be susceptible to long-term damage.